Legal Protection for Victims of Photo Abuse through Artificial Intelligence Technology in Pornography Crimes in Indonesia - Aruan , Juandry (Semarang State University Undergraduate Law and Society Review, 2025)
The development of artificial intelligence (AI) technology has given birth to a new form of crime in the form of deepfake pornography, which is the production of sexual content that is digitally manipulated without the consent of the subject. This article discusses legal protection for victims of deepfake pornography in Indonesia through normative juridical approaches and case studies, particularly by highlighting the case of Udayana University students who produced deepfake content against dozens of female students. The results of the study show that Indonesia’s positive law—through the Pornography Law, the ITE Law, and the TPKS Law—has not specifically regulated the crime of producing AI-engineered content, so law enforcement officials often have difficulty in ensnaring perpetrators optimally. In addition, technical constraints, weak digital forensic capacity, social stigma, and low digital literacy worsen the position of victims. This article recommends a reformulation of regulations that include explicit definitions of deepfake content, strengthening impact-based criminal sanctions, restitution for victims, national digital education, and the establishment of international cooperation through the ratification of the Budapest Convention. With a comprehensive legal approach and oriented towards victim protection, it is hoped that the Indonesian legal system will be able to answer the challenges of digital crime in the era of artificial intelligence.